Reclaiming the mind: the urgency of islamising human knowledge - Datu Jafri, Fakhira; Amir Abdullah, Mazwa Rabytah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The Islamisation of Human Knowledge is a crucial initiative to restore the Islamic worldview in contemporary thought. First introduced by Syed Muhammad Naquib al-Attas in the 1970s and later expanded by Ismail Raji al-Faruqi, it involves reinterpreting all forms of knowledge through an Islamic lens. This process aims to counter the influence of secular ideologies and realign education with the moral and spiritual values rooted in the Qur’an and Sunnah.